Tides of Connection: Exploring Human-River/Sea Relationships in Children's Short Stories through an Ecocritical Lens - Amalia Kurnia Devi (Lingua Susastra, 2024)
Through an ecocritical perspective, this paper investigates the issue of ecological consciousness in children's literature from Southeast Asia. With a focus on four tales from Malaysia, Singapore, Vietnam, and Indonesia, the study explores the interaction between people and the environment—more specifically, rivers and oceans. The purpose of the study is to expose anthropocentrism and how it affects human existence in these stories. The study uses content analysis in conjunction with a descriptive qualitative method to look for recurring themes and patterns in the chosen stories. The portrayal of human-environment links in each narrative is examined in depth in the first section of the examination. The role of rivers and oceans as allies and adversaries is examined in the second section. By analyzing various Southeast Asian viewpoints, this study adds to our understanding of ecological consciousness in children's literature and illuminates the complex interactions that exist in the area between the environment and humankind.